Defining usual physiotherapy care in ambulant children with cerebral palsy in the United Kingdom: A mixed methods consensus study - Rapson, R.; Latour, Jos; Marsden, J.; Hughes, H.; Carter, B. (2022)
Background: Ambulant children with cerebral palsy (CP) undertake physiotherapy to improve balance and walking. However, there are no relevant clinical guidelines to standardize usual physiotherapy care in the United Kingdom. A consensus process can be used to define usual physiotherapy care for children with CP. The resulting usual care checklist can support the development of clinical guidelines and be used to measure fidelity to usual care in the control groups of trials for children with CP. Methods: Twelve expert physiotherapists were recruited. In Phase 1, statements on usual care were developed using a survey and two nominal groups. Phase 2 included a literature review to support usual physiotherapy interventions. Phase 3 used a confirmatory survey, which also captured changes to provision during the COVID-19 pandemic. Consensus was calculated by deriving the mean of the deviations from the median score (MDM). High consensus was deemed to be where MDM < 0.42. Results: Physiotherapists reached high consensus on five outcome measures (MDM range 0–0.375) and nine areas of assessment (MDM range 0–0.25). Physiotherapists reached moderate consensus on task-specific training (MDM = 0.75), delivered at weekly intensity for 4–6 weeks (MDM = 0.43). There was high consensus (MDM = 0) that children should participate in modified sport and fitness activities and that children with Gross Motor Function Classification System Level III should be monitored on long-term pathways (MDM = 0.29). Conclusions: Physiotherapists reached consensus on two usual care interventions, and a checklist was developed to inform the control groups of future randomized controlled trials. Further consensus work is required to establish clinical guidelines to standardize usual physiotherapy care in the United Kingdom.